2008
DOI: 10.4049/jimmunol.181.12.8323
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Innate Immune Response through TLR2 and Dectin 1 Prevents Type 1 Diabetes

Abstract: Studies have suggested a correlation between the decline in infectious diseases and increase in the incidence of type 1 diabetes (T1D) in developed countries. Pathogens influence the disease outcome through innate immune receptors such as TLRs. Here we report the effect of ligation of TLR2 and dectin 1 on APCs and the influence of innate immune response induced through these receptors on T1D. Exposure of APCs of NOD mice to zymosan, a fungal cell wall component that interacts with TLR2 and dectin 1, resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 75 publications
(92 reference statements)
7
91
2
Order By: Relevance
“…It should be noted that we used adjuvants without autoantigens in our protection model. It has been shown that multiple injections of zymosan, three times in the first week and injection in weeks 3, 5, 7, 9, and 11, could prevent diabetes development (37). We just used a single injection of zymosan.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that we used adjuvants without autoantigens in our protection model. It has been shown that multiple injections of zymosan, three times in the first week and injection in weeks 3, 5, 7, 9, and 11, could prevent diabetes development (37). We just used a single injection of zymosan.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments showed that zymozan treatment resulted in a decrease in immune cell infiltrate in b-islets, reduced b-islet destruction, increased naive or regulatory T cell phenotype and enhanced regulatory T suppressor function. 93 TLR-2 and Dectin-1 ligation by zymosan was shown to induce IL-10 and TGF-b expression, but it is unclear if these results are solely due to suppressive cytokine expression. Taken together, these data suggest that CLR targeting may induce immune tolerance through the induction of regulatory T cells, or by enhancing the activity of existing regulatory T cells.…”
Section: Targeting Clrs For Immunotherapymentioning
confidence: 99%
“…Complete Freund's adjuvant [84] Streptococcal OK-432 [85] Klebsiella pneumonia glycoprotein [86] Escherischia coli LPS [86] Zymosan [87] Zymosan [88] CpG DNA [89] CpG DNA [90] Polyinosinic:polycytidylic acid [80] OM-85 (multi-species extract) [91] Pseudomonas aeruginosa OdDHL [92] Legend: LNFPIII -lacto-N-fucopentaose III, BCG -baccilus calmette-guerin, LPS -lipopolysaccharide, OdDHL -N-(3-oxododecanoyl)-L-homoserine lactone.…”
Section: Bovis Bcg [82 83]mentioning
confidence: 99%